Bałtycka Biblioteka Cyfrowa (BBC) - informacja regionalna w sieci = Baltic Digital Library (BBC) - regional information on the web - Sroka, Danuta Maria (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The paper presents tools and methods related to the creation and dissemination of regional information on the basis of the Baltic Digital Library (BBC). The usefulness of the BBC in the context of information retrieval is pointed out, and the author attempts to define the digital library as a regional digital repository, which is only used when there is an appropriate mechanism for organizing and searching its resources. Its functions are outlined as well as the roles it plays in the digital information space.The first part discusses the changes that have taken place in the functioning of traditional libraries, points out the values of regionalism, the variety of types and forms of regional documents and the cooperation in acquiring a resource for digitization. The second part underlines the development of the Baltic Digital Library and presents the factors influencing its effectiveness and efficiency in terms of automatic information processing and transmission. Attention is also paid to methods of digital presentation.
Keywords: Bałtycka Biblioteka Cyfrowa; biblioteka cyfrowa; digitalizacja; sieciowanie; biblioteka publiczna; archiwizacja; wiedza; Słupsk; metadane; informacja; książka cyfrowa; Architektura IT; usługi cyfrowe; hybrydyzacja; wieloformatowy; Federacja Bibliotek Cyfrowych; Europeana; dLibra; regionalizm; obiekty cyfrowe; Baltic Digital Library; digital library; digitization; networking; public library; archiving; knowledge; metadata; information; digital book; IT architecture; digital services; hybridization; multi-format; Digital Library Federation; regionalism; digital objects